EPILEPSY SEIZURE DETECTION USING WAVELET BASED BY ARTIFACT REDUCTION - MISS. NEHA J. SURYAWANSHI,; MR. S.S.PAWAR, (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents a method to remove artifacts from scalp EEG recordings to diagnosis/ detect seizure in epilepsy patients.Epilepsy is a neurological disorder in which the nerves in the brain communicate abnormally with each other. The proposed algorithm isbased on stationary wavelet transform and takes the spectral band of seizure activities into account to remove artifacts in seizures. The features of EEG signal responsile for the detection of seizures from non seizure epochs have been found to be easily distinguishable after artifacts are removed and consequently the false alarms in seizure detection are reduced.